2021
DOI: 10.1002/path.5618
|View full text |Cite
|
Sign up to set email alerts
|

Induced hepatic stellate cell integrin, α8β1, enhances cellular contractility and TGFβ activity in liver fibrosis

Abstract: No effective therapy exists for fatal fibrosis. New therapeutic targets are needed for hepatic fibrosis because the incidence keeps increasing. The activation and differentiation of fibroblasts into myofibroblasts that causes excessive matrix deposition is central to fibrosis. Here, we investigated whether (and which) integrin receptors for matrix proteins activate hepatic stellate cells (HSCs). First, integrin α‐subunits were investigated systematically for their expression over the course of HSC activation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 32 publications
2
47
0
Order By: Relevance
“…Corresponded with the current results, up-regulated ITGA8 was previously reported in broiler breast muscle affected by WS abnormality ( Marchesi et al, 2019 ), and in specimen of 90 patients with hepatic fibrosis ( Nishimichi et al, 2021 ). In addition, the same authors found that ITGA8 was minimally expressed in healthy liver, underlying its relevance with liver fibrosis.…”
Section: Discussionsupporting
confidence: 92%
“…Corresponded with the current results, up-regulated ITGA8 was previously reported in broiler breast muscle affected by WS abnormality ( Marchesi et al, 2019 ), and in specimen of 90 patients with hepatic fibrosis ( Nishimichi et al, 2021 ). In addition, the same authors found that ITGA8 was minimally expressed in healthy liver, underlying its relevance with liver fibrosis.…”
Section: Discussionsupporting
confidence: 92%
“…Several lines of evidence support ITGA8 as a contributing factor to fibrosis development. [47][48][49][50] In liver disease, Liu et al indicated that ITGA8 expression is increased in patients with non-alcoholic fatty liver disease (NAFLD) and in mice. Furthermore, they found that ITGA8 is involved in the pathogenesis of liver fibrosis in the course of NAFLD via the RhoA signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Integrin α8β1, unlike to most other integrins, shows characteristic restricted expression in mesenchymal cells [61]. A comprehensive gene expression data for 150 primary cells from various tissues [62] reveals α8 subunit is selectively expressed on fibroblasts (Figure 4) [11]. Only α1, α8 and α11 subunit in all the 18 α and 8 β subunits of the integrin family show the fibroblast selective pattern, and α8 is most fibroblast selective as shown in Figure 4.…”
Section: Disease Specific Integrinsmentioning
confidence: 99%
“…Furthermore, the fibroblast-selective expression of α8 is highly upregulated by a stimulus mimicking fibrosis. α8 in hepatic stellate cells (HSCs) either from rat or mouse is significantly induced both at the mRNA and protein levels [11] by culture activation for 14 days (Figure 5). HSCs are known to be activated by in vitro culture as in fibrotic tissue, associated with elevation of fibrosis markers such as α-smooth muscle actin (α-SMA).…”
Section: Disease Specific Integrinsmentioning
confidence: 99%
See 1 more Smart Citation